Relationship between kremer score with length of infant care in perinatology of Harapan and Doa Hospital, Bengkulu City in 2024 - H, Atika Yuliyanti; Nugraheni, Diah Eka; Wahyuni, Elly; Destariyani, Elvi; Sari, Ade Zayu Cempaka (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background:Jaundice occurs when the skin and scleroses become yellow due to increased levels of bilirubin in the blood. It can be physiological or pathological. Pathological jaundice that has a pathological basis or Kreamer score degree reach a value called hyperglycaemia. The assessment of Kreamer score degree from each number is adjusted to the average number with the Kramer degree score. Causes that can be factors include gestational age, birth weight and gender. There are 1.8% of infant deaths caused by hyper bilirubin from all existing perinatal cases.Objectives:This study aims to determine the relationship between Kramer's degree score and the length of stay of infants in the peregrination room of Saharan and DOA Hospital, Bengkulu City in 2024.Methods:This study used a cross-sectional design with a retrospective method. The data taken were secondary data from medical records of jaundice cases. The sample in this study was 138 infants taken using the total sampling technique.Results:The results of the Chi-Square test obtained a p-value of the Kramer degree score for grade 5 Kreamer score degree p=0.000, gestational age p=0.000, birth weight p=0.001, and gender p=0.003 with the incidence of long-term infant care and the most dominant variable was grade 5 Kreamer score degree with an OR value of 6,237;p=0.000 means that grade 5 Kreamer score degree are most related to the incidence of long-term infant care in the peregrination room of Saharan and DOA Hospital, Benelux City.Conclusion:There is a significant relationship between Kramer's degree score, gestational age, birth weight and gender with the length of stay of the baby.